The genome-wide supported CACNA1C gene polymorphisms and the risk of schizophrenia: an updated meta-analysis - Yong-ping Liu; Xue Wu; Xi Xia; Jun Yao; Bao-jie Wang (BMC, 2020)
Abstract Background The CACNA1C gene was defined as a risk gene for schizophrenia in a large genome-wide association study of European ancestry performed by the Psychiatric Genomics Consortium. Previous meta-analyses focused on the association between the CACNA1C gene rs1006737 and schizophrenia. The present study focused on whether there was an ancestral difference in the effect of the CACNA1C gene rs1006737 on schizophrenia. rs2007044 and rs4765905 were analyzed for their effect on the risk of schizophrenia. Methods Pooled, subgroup, sensitivity, and publication bias analysis were conducted. Results A total of 18 studies met the inclusion criteria, including fourteen rs1006737 studies (15,213 cases, 19,412 controls), three rs2007044 studies (6007 cases, 6518 controls), and two rs4765905 studies (2435 cases, 2639 controls). An allele model study also related rs2007044 and rs4765905 to schizophrenia. The overall meta-analysis for rs1006737, which included the allele contrast, dominant, recessive, codominance, and complete overdominance models, showed significant differences between rs1006737 and schizophrenia. However, the ancestral-based subgroup analysis for rs1006737 found that the genotypes GG and GG + GA were only protective factors for schizophrenia in Europeans. In contrast, the rs1006737 GA genotype only reduced the risk of schizophrenia in Asians. Conclusions Rs1006737, rs2007044, and rs4765905 of the CACNA1C gene were associated with susceptibility to schizophrenia. However, the influence model for rs1006737 on schizophrenia in Asians and Europeans demonstrated both similarities and differences between the two ancestors.